Polymer film and method for producing same

By using a combination of soluble liquid crystal polyester (A), polymer (B) and insoluble liquid crystal polyester (C) in polymer films, the problems of poor signal transmission and degradation of mechanical properties in high-frequency applications are solved, and efficient coating and low moisture permeability are achieved.

CN119708768APending Publication Date: 2025-03-28CHI MEI CORP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411325499.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-09-27
Filing Date
2024-09-23
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing polymer films have problems with poor signal transmission in 5G high-frequency applications, and their mechanical properties decrease during processing and bonding, tend to deform, poor coating properties and excessive moisture permeability.

Method used

The polymer film including soluble liquid crystal polyester (A), polymer (B) and insoluble liquid crystal polyester (C) is used to improve the coating, flexibility and low moisture permeability of the film through specific compound composition and manufacturing methods.

Benefits of technology

Good coating properties, improved flexibility and low moisture permeability of polymer films are achieved, and the problems of degradation of mechanical properties and excessive moisture permeability in the prior art are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005055311950000031
    Figure BDA0005055311950000031
  • Figure BDA0005055311950000041
    Figure BDA0005055311950000041
  • Figure BDA0005055311950000061
    Figure BDA0005055311950000061
Patent Text Reader

Abstract

The invention provides a polymer film and a manufacturing method thereof. The polymer film comprises soluble liquid crystal polyester (A), polymer (B) and insoluble liquid crystal polyester (C). The soluble liquid crystal polyester (A) is obtained by reacting a first mixture, and the first mixture comprises aromatic and aromatic hydroxycarboxylic acid (a1), aromatic dicarboxylic acid (a2), aromatic amine (a3) with phenolic hydroxyl and aromatic diol (a4). The polymer (B) is selected from at least one of a group consisting of a polyimide precursor and an imidized polymer of the polyimide precursor, the polymer (B) is obtained by reacting a second mixture, and the second mixture comprises a tetracarboxylic dianhydride component (b1) and a diamine component (b2). Therefore, the polymer film has good coating property, flexibility and low moisture permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polymer film and a method for making the same, in particular to a liquid crystal polyester polymer film and a method for making the same. Background Art

[0002] Although polyimide has better film processability and temperature resistance, it has the disadvantages of poor electrical properties and high water absorption, so it will have the problem of poor signal transmission in 5G high-frequency applications.

[0003] A known polymer film used in high frequency applications is made of an insoluble liquid crystal polymer, that is, the liquid crystal polymer is insoluble in solvents, has good electrical properties, and has low water absorption. However, due to its high melting point, when the processing temperature is close to the liquid crystal temperature (about 280°C to about 330°C), the mechanical properties of the obtained liquid crystal polyester film will drop sharply, resulting in the film being very difficult to process in conjunction with copper foil when used in high frequency applications, and the liquid crystal polyester film is prone to deformation after a high temperature bonding process. Furthermore, the liquid crystal polyester film has high crystallinity and molecular alignment, so during the film-making process, the molecular arrangement is easily in the same direction as the coating direction, which ultimately results in a large difference in the mechanical properties of the film in the vertical / horizontal direction, and even the film is prone to brittle cracks in the non-coating direction, which is quite difficult to manufacture.

[0004] Therefore, the conventional polymer film still has problems of poor flexibility, poor coating performance and excessively high moisture permeability. In view of this, it is urgent to provide a polymer film and a manufacturing method thereof to improve the aforementioned problems. Summary of the invention

[0005] In view of this, one aspect of the present invention provides a polymer film, which includes a soluble liquid crystal polyester (A), a polymer (B) and an insoluble liquid crystal polyester (C).

[0006] Another aspect of the present invention is to provide a method for manufacturing a polymer film line, which is used to prepare the polymer film of the above aspect.

[0007] One aspect of the present invention provides a polymer film, which includes a soluble liquid crystal polyester (A), a polymer (B) and an insoluble liquid crystal polyester (C). The soluble liquid crystal polyester (A) is obtained by reacting a first mixture, the first mixture includes an aromatic hydroxycarboxylic acid (a1), an aromatic dicarboxylic acid (a2), an aromatic amine having a phenolic hydroxyl group (a3) ​​and an aromatic diol (a4). The polymer (B) is at least one selected from the group consisting of a polyimide precursor and an imidized polymer of a polyimide precursor, and the polymer (B) is obtained by reacting a second mixture, the second mixture includes a tetracarboxylic dianhydride component (b1) and a diamine component (b2).

[0008] According to one embodiment of the present invention, the soluble liquid crystal polyester (A) comprises at least one of the structural units of the following formula (a1'), formula (a2'), formula (a3') and formula (a4'),

[0009] -O-Ar 1 -CO- (a1')

[0010] -CO-Ar 2 -CO- (a2')

[0011] -NH-Ar 3 -O- (a3')

[0012] -O-Ar 3 -O- (a4')

[0013] In formula (a1'), Ar 1 represents a phenylene group, a naphthylene group or a biphenylene group;

[0014] In formula (a2'), Ar 2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group formed by condensation of a plurality of aromatic groups; and

[0015] In formula (a3') and formula (a4'), Ar 3 It represents a phenylene group or a group formed by condensation of a plurality of aromatic groups.

[0016] According to one embodiment of the present invention, the aromatic amine (a3) ​​having a phenolic hydroxyl group comprises an aromatic hydroxyamide.

[0017] According to an embodiment of the present invention, the polymer (B) includes an ester structure.

[0018] According to an embodiment of the present invention, the tetracarboxylic dianhydride component (b1) includes a tetracarboxylic dianhydride compound (b1-1) containing an ester group.

[0019] According to one embodiment of the present invention, the diamine component (b2) includes a diamine compound (b2-1) containing an ester group.

[0020] According to an embodiment of the present invention, based on 100 wt % of the polymer film, the content of the soluble liquid crystal polyester (A) is 20 wt % to 90 wt %.

[0021] According to an embodiment of the present invention, based on 100 wt % of the polymer film, the content of the polymer (B) is not less than 3 wt %.

[0022] According to an embodiment of the present invention, based on 100 wt % of the polymer film, the content of the insoluble liquid crystal polyester (C) is 5 wt % to 70 wt %.

[0023] According to an embodiment of the present invention, the aromatic diol (a4) is at least one compound selected from the group consisting of compounds including the following structural units.

[0024]

[0025]

[0026] Another aspect of the present invention is to provide a method for manufacturing a polymer film, which can produce the above-mentioned polymer film. The method includes a coating step to coat a liquid composition on a substrate, wherein the liquid composition includes a soluble liquid crystal polyester (A), a polymer (B), an insoluble liquid crystal polyester (C) and a solvent. The method also includes a heating step to heat the substrate coated with the liquid composition, wherein the heating temperature of the heating step is greater than 300°C.

[0027] The polymer film of the present invention comprises a specific soluble liquid crystal polyester (A), a polymer (B) and an insoluble liquid crystal polyester (C), and thus has good coating properties, flexibility and low moisture permeability. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] none DETAILED DESCRIPTION

[0029] [Soluble liquid crystal polyester (A)]

[0030] The soluble liquid crystal polyester (A) of the present invention is prepared by reacting a first mixture. The first mixture comprises an aromatic hydroxycarboxylic acid (a1), an aromatic dicarboxylic acid (a2), an aromatic amine having a phenolic hydroxyl group (a3) ​​and an aromatic diol (a4). Specifically, the soluble liquid crystal polyester (A) of the present invention preferably comprises structural units of the following formula (a1'), formula (a2'), formula (a3') and formula (a4').

[0031] -O-Ar 1 -CO- (a1')

[0032] -CO-Ar 2 -CO- (a2')

[0033] -NH-Ar 3 -O- (a3')

[0034] -O-Ar 3 -O- (a4')

[0035] In formula (a1'), Ar 1 represents a phenylene group, a naphthylene group or a biphenylene group;

[0036] In formula (a2'), Ar 2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group formed by condensation of a plurality of aromatic groups; and

[0037] In formula (a3') and formula (a4'), Ar 3 It represents a phenylene group or a group formed by condensation of a plurality of aromatic groups.

[0038] It should be noted that the above-mentioned "structural unit of formula (a1')" is derived from the structure of the above-mentioned "aromatic hydroxycarboxylic acid (a1)". The above-mentioned "structural unit of formula (a2')" is derived from the structure of the above-mentioned "aromatic dicarboxylic acid (a2)". The above-mentioned "structural unit of formula (a3')" is derived from the structure of the above-mentioned "aromatic amine having phenolic hydroxyl group (a3)". The above-mentioned "structural unit of formula (a4')" is derived from the structure of the above-mentioned "aromatic diol (a4)".

[0039] In some embodiments, the compound having the formula (a3′) comprises an aromatic hydroxyamide. When the soluble liquid crystal polyester (A) comprises an aromatic hydroxyamide structure, it can have a higher molecular weight, increase viscosity, and adjust coating properties.

[0040] Hereinafter, the compounds contained in the first mixture for preparing the soluble liquid crystal polyester (A) will be described in detail.

[0041] [Aromatic hydroxycarboxylic acid (a1)]

[0042] The aromatic hydroxycarboxylic acid (a1) may include structural units represented by the following formulae (a1′-1) to (a1′-5), wherein the aromatic ring may be substituted by a halogen atom, an alkyl group or an aromatic group.

[0043]

[0044] In formula (a1'-1) to formula (a1'-5), the alkyl group as the substituent in the aromatic ring is usually an alkyl group having 1 to 10 carbon atoms, preferably methyl, ethyl, n-propyl, or n-butyl. The aromatic group as the substituent in the aromatic ring is usually an aromatic group having 6 to 20 carbon atoms, preferably phenyl.

[0045] In some specific examples, the aromatic hydroxycarboxylic acid (a1) may be, for example, p-hydroxybenzoic acid, m-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4-hydroxy-1-naphthoic acid or 4-(4-hydroxyphenyl)benzoic acid.

[0046] [Aromatic dicarboxylic acid (a2)]

[0047] The aromatic dicarboxylic acid (a2) may include structural units as shown in the following formulas (a2'-1) to (a2'-10), wherein the aromatic ring may be substituted by a halogen atom, an alkyl group or an aromatic group. The specific substituents are the same as those listed for the aromatic hydroxycarboxylic acid (a1) above, and will not be described in detail here.

[0048]

[0049]

[0050] In some specific examples, the aromatic dicarboxylic acid (a2) may be, for example, terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, biphenyl-4,4'-dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, diphenyl sulfide-4,4'-dicarboxylic acid, diphenyl sulfone-4,4'-dicarboxylic acid, dibenzophenone-4,4'-dicarboxylic acid, etc.

[0051] [Aromatic amine having phenolic hydroxyl group (a3)]

[0052] The aromatic amine (a3) ​​having a phenolic hydroxyl group may include structural units as shown in the following formulas (a3'-1) to (a3'-6), wherein the aromatic ring may be substituted by a halogen atom, an alkyl group or an aromatic group. The specific substituents are the same as those listed for the aromatic hydroxycarboxylic acid (a1) above, and will not be described in detail here.

[0053]

[0054] In some specific examples, the aromatic amine (a3) ​​having a phenolic hydroxyl group may be, for example, an aromatic hydroxylamine and an aromatic hydroxyamide. Aromatic hydroxylamines may be, for example, 3-aminophenol, 4-aminophenol, 4-amino-4'-hydroxybiphenyl, etc. Aromatic hydroxyamides may be, for example, 3-hydroxyacetanilide, 4-hydroxyacetanilide, etc. If the aromatic amine (a3) ​​having a phenolic hydroxyl group includes an aromatic hydroxyamide, the obtained soluble liquid crystal polyester (A) may have a higher molecular weight, and the viscosity may be increased and the coating properties may be adjusted.

[0055] [Aromatic diol (a4)]

[0056] The aromatic diol (a4) may include structural units as shown in the following formula (a4'-1) to formula (a4'-11), wherein the aromatic ring may be substituted by a halogen atom, an alkyl group or an aromatic group. The specific substituents are the same as those listed for the aromatic hydroxycarboxylic acid (a1) above, and are not described in detail here. If the aromatic diol (a4) includes structural units as shown in the following formula (a4'-6) to formula (a4'-11), the polymer film may have better flexibility.

[0057]

[0058]

[0059] In some specific examples, the aromatic diol (a4) may be, for example, hydroquinone, resorcinol, 2,6-naphthalene diol, 1,5-naphthalene diol, 4,4'-biphenyl diol, biphenyl-2,5-diol, 2,2-bis(4-hydroxyphenyl)propane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 4,4'-dihydroxydiphenyl ether, bis-(4-hydroxyphenyl) ketone, bis-(4-hydroxyphenyl) sulfone, 4,4'-dihydroxydiphenylmethane, etc.

[0060] [Usage amount of each compound of soluble liquid crystal polyester (A)]

[0061] The amount of the aromatic hydroxycarboxylic acid (a1) compound used is 10 mol% to 75 mol%, preferably 15 mol% to 70 mol%, and more preferably 20 mol% to 65 mol%, relative to the first mixture of the soluble liquid crystal polyester (A). The amount of the aromatic dicarboxylic acid (a2) used is 5 mol% to 50 mol%, preferably 10 mol% to 45 mol%, and more preferably 15 mol% to 40 mol%, relative to the first mixture of the soluble liquid crystal polyester (A).

[0062] The amount of the aromatic amine (a3) ​​having a phenolic hydroxyl group is 3 mol% to 45 mol%, preferably 5 mol% to 40 mol%, and more preferably 8 mol% to 35 mol% relative to the first mixture for preparing the soluble liquid crystal polyester (A). If the aromatic amine (a3) ​​having a phenolic hydroxyl group is not included in the first mixture for preparing the soluble liquid crystal polyester (A), the coating property of the polymer film is poor.

[0063] The amount of the aromatic diol (a4) used relative to the first mixture of the soluble liquid crystal polyester (A) is 3 mol% to 35 mol%, preferably 5 mol% to 30 mol%, and more preferably 8 mol% to 25 mol%. If the first mixture of the soluble liquid crystal polyester (A) does not contain the aromatic diol (a4), the flexibility and coating properties of the polymer film are poor.

[0064] In the first mixture for preparing the soluble liquid crystal polyester (A), the aromatic hydroxycarboxylic acid (a1), the aromatic dicarboxylic acid (a2), the aromatic amine having a phenolic hydroxyl group (a3) ​​and the aromatic diol (a4) may contain only one or more than two of each. In addition, the first mixture for preparing the soluble liquid crystal polyester (A) may contain other compounds other than the aromatic hydroxycarboxylic acid (a1), the aromatic dicarboxylic acid (a2), the aromatic amine having a phenolic hydroxyl group (a3) ​​and the aromatic diol (a4), and the other compounds are preferably 10 mol% or less, more preferably 5 mol% or less relative to the first mixture.

[0065] [Method for producing soluble liquid crystal polyester (A)]

[0066] The method for producing the soluble liquid crystal polyester (A) of the present invention is not particularly limited. For example, an acylate can be obtained by acylation of an aromatic hydroxycarboxylic acid (a1), an aromatic amine (a3) ​​having a phenolic hydroxyl group, and an aromatic diol (a4) with an excess of fatty acid anhydride. The acylate is then polymerized with an aromatic hydroxycarboxylic acid (a1) and / or an aromatic dicarboxylic acid (a2) through an ester exchange / amide exchange reaction to obtain the soluble liquid crystal polyester (A).

[0067] In the acylation reaction, the amount of fatty acid anhydride added is preferably 1.0 to 1.2 times the total amount of phenolic hydroxyl groups and amine groups, and more preferably 1.05 to 1.1 times the equivalent. If the amount of fatty acid anhydride added is too little, the reaction apparatus tends to be blocked due to the sublimation of the acylate or other reactants during polymerization reactions such as transesterification or transamide exchange; if the amount of fatty acid anhydride added is too much, the soluble liquid crystal polyester (A) obtained is easily colored. As the reaction conditions for the acylation reaction, it is preferably reacted at 130°C to 180°C for 5 minutes to 10 hours, and more preferably reacted at 140°C to 160°C for 10 minutes to 3 hours.

[0068] In the acylation reaction, the fatty acid anhydride used is not particularly limited, and can be enumerated: diacetic anhydride, propionic anhydride, butyric anhydride, isobutyric anhydride, valeric anhydride, pivalic anhydride, 2-ethylhexanoic anhydride, dichloroacetic anhydride, trichloroacetic anhydride, monobromoacetic anhydride, dibromoacetic anhydride, tribromoacetic anhydride, monofluoroacetic anhydride, difluoroacetic anhydride, trifluoroacetic anhydride, glutaric anhydride, maleic anhydride, succinic anhydride, β-bromopropionic anhydride etc. Fatty acid anhydride can only use one or use two or more. From the viewpoint of price and operability, preferably diacetic anhydride, propionic anhydride, butyric anhydride or isobutyric anhydride, more preferably diacetic anhydride.

[0069] In the transesterification / amidation reaction, the acyl content of the acylate is preferably 0.8 to 1.2 times the equivalent relative to the carboxyl content. As the reaction temperature of the transesterification / amidation reaction, it is preferably below 400°C, and more preferably below 350°C. In addition, the heating rate of the reaction is preferably 0.1 to 50°C / minute, and more preferably 0.3 to 5°C / minute. In addition, in order to shift the equilibrium between the reactants and the products, it is preferred to distill the by-product fatty acids or unreacted fatty acid anhydrides from the reaction system by evaporation or the like during the reaction. In addition, the acylation reaction and the transesterification / amidation reaction can be carried out in the presence of a catalyst. As a catalyst, substances that are known as catalysts for polyester polymerization can be used, such as metal salts such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, antimony trioxide, and organic compounds such as N,N-dimethylaminopyridine and N-methylimidazole. The catalyst is usually present during the acylation reaction, and even after the acylation reaction, it is not necessary to remove the catalyst. If the catalyst is not removed, the next treatment can be directly performed. In addition, the above catalyst can be further added when performing the next treatment.

[0070] The polymerization reaction of the transesterification / amidation reaction is usually carried out by melt polymerization, but melt polymerization and solid phase polymerization can also be used in combination. Solid phase polymerization can be carried out by a known solid phase polymerization method after extracting the polymer from the melt polymerization step, solidifying it and crushing it into powder or flakes. Specifically, it can be listed as a method of heat treatment in a solid phase state at 20°C to 350°C under a nitrogen environment for 1 hour to 30 hours. Solid phase polymerization can be carried out under stirring or in a static state without stirring. In addition, as long as an appropriate stirring mechanism is provided, the melt polymerization tank and the solid phase polymerization tank can be the same reaction tank. After solid phase polymerization, the obtained liquid crystal polyester can be granulated by a known method.

[0071] [Polymer (B)]

[0072] The polymer film of the present invention further comprises a polymer (B) so that the polymer film has better flexibility. If the polymer film does not comprise a polymer (B), the flexibility of the polymer film is poor.

[0073] The polymer (B) is at least one selected from the group consisting of a polyimide precursor and an imidized polymer of the polyimide precursor, wherein the polyimide precursor includes an ester structure. If the polymer (B) does not include an ester structure, the compatibility of the soluble liquid crystal polyester (A) and the polymer (B) is poor, and the coating property is poor.

[0074] The polyimide precursor is obtained by reacting the second mixture, and the second mixture includes a tetracarboxylic dianhydride component (b1) and a diamine component (b2). The tetracarboxylic dianhydride component (b1) may include an ester-containing tetracarboxylic dianhydride (b1-1), and the diamine component (b2) may include an ester-containing diamine (b2-1). If the second mixture includes an ester-containing tetracarboxylic dianhydride (b1-1) and an ester-containing diamine (b2-1), the polymer film may have better coating properties.

[0075] The ester group-containing tetracarboxylic dianhydride (b1-1) or ester group-containing diamine (b2-1) monomer preferably accounts for more than 20% of the molar number of the polyimide, and more preferably accounts for more than 50% of the molar number of the polyimide.

[0076] The ester-containing tetracarboxylic dianhydride (b1-1) may be, for example, p-phenylene bis(trimellitate) dianhydride, cyclohexane-1,4-diylbis(methylene)bis(trimellitate) dianhydride, ethylene bis(trimellitate) dianhydride, propyl bis(trimellitate) dianhydride or (4-phthalic anhydride) formyloxy-4-phthalic anhydride (5-Isobenzofurancarboxylicacid, 1,3-dihydro-1,3-dioxo-, 1,3-dihydro-1,3-dioxo-5-isobenzofuranylester).

[0077] The ester-containing diamine (b2-1) may be, for example, 4-aminobenzoic acid 4-aminophenyl ester, bis(4-aminophenyl terephthalate) (1,4-Benzenedicarboxylic acid bis(4-aminopheny1) ester) or [4-(4-aminobenzoyl)oxyphenyl] 4-aminobenzoate (1,4-Benzenedicarboxylic acid bis(4-aminopheny1) ester).

[0078] In addition to the ester-containing tetracarboxylic dianhydride (b1-1) and the ester-containing diamine (b2-1), other types of monomers can also be selected to match the ester-containing monomer to adjust the desired properties. Other tetracarboxylic dianhydrides (b1-2) without ester groups can be selected from 1,2,4,5-Benzenetetracarboxylicanhydride (PMDA), 3,3',4,4'-biphenyltetracarboxylicdianhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA), 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride) (b1-2). exafluoropropanedianhydride, 6-FDA), 3,3',4,4'-benzophenonetetracarboxylicdianhydride (Benzophenone-3,3',4,4'-tetracarboxylicdianhydride, BTDA), 1,2,3,4-cyclobutanetetracarboxylicdianhydride (1,2,3,4-cyclobutanetetracarboxylicdianhydride, CBDA), 4,4'-(4,4'-isopropylidene-diphenoxy)bis(ph t halicanhydride), BPADA), 2,3,3',4'-biphenyltetracarboxylicdiandhydride (α-BPDA), etc.

[0079] Other diamines (b2-2) without ester groups can be selected from p-phenylenediamine (1,4-diaminobenzene, PDA), 4,4'-diaminodiphenyl ether (4,4'-diaminodiphenylether, ODA), 3,4'-diaminodiphenyl ether (3,4'-diaminodiphenylether, 34ODA), 1,3-phenylenediamine (1,3-diaminobenzene, mPDA), 4,4'-diaminodiphenylsulfone (44DDS), 3,3'-diaminodiphenylsulfone (3,3'-diaminodiphenylsulfone, 44DDS), 4,4'-diaminodiphenylsulfone ( ... phenylsulfone, 33DDS), 4,4'-diamino-2,2'-dimethyl-1,1'-biphenyl (2,2'-dimethy1[1,1'-bipheny1]-4,4'-diamine, mTB), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl (2,2'-bis(trifluoromethy1)-4,4'-diaminobiphenyl, TFMB), 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane (2,2-bis[4-(4-aminophenoxy)phenyl]

[0080] hexafluoropropane, HFBAPP), 2,2-bis(trifluoromethyl)-4,4'-diaminodiphenylether (6FODA), 2,2'-bis[4-(4-aminophenoxyphenyl)]propane (BAPP), 1,3-bis(3-aminophenoxy)benzene (APB-N), 4,4'-bis(4-aminophenoxy)biphenyl (BAPB), 1,3-bis(4-aminophenoxy)benzene ... 1,3,bis(4'-aminophenoxy)benzene (TPER), 1,4-bis(4-aminophenoxy)benzene (TPEQ), 4,4'-diaminobenzanilide (44DABA), 2-(4-aminophenyl)-5-aminobenzoxazole (5BPOA), N,N'-(2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diyl)-bis(4-aminobenzamide) (N,N'-[2,2'-bis(trifluoromethyl)-[1,1'-biphenyl]-4,4'-diyl)-bis(4-aminobenzamide)

[0081] [1,1'-bipheny1]-4,4'-diy1]bis[4-aminobenzamide], AB-TFMB).

[0082] [Method for producing polyamic acid]

[0083] The preparation method of polyamic acid comprises the following steps: firstly dissolving a mixture in a solvent, wherein the mixture comprises a tetracarboxylic dianhydride component (b1) and a diamine component (b2), and carrying out a polymerization reaction at a temperature of 0°C to 100°C for 1 hour to 24 hours. Then, the reaction solution is subjected to reduced pressure distillation by an evaporator to obtain polyamic acid, or the reaction solution is poured into a large amount of poor solvent to obtain a precipitate. Then, the precipitate is dried by reduced pressure drying to obtain polyamic acid.

[0084] The solvent used in the polymerization reaction is not particularly limited, as long as it can dissolve the reactants and products. Preferably, the solvent includes but is not limited to (1) aprotic polar solvents: N-methyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, tetramethyl urea or hexamethylphosphoric acid triamide, etc.; (2) phenolic solvents: m-cresol, xylenol, phenol or halogenated phenols, etc. Preferably, based on the total amount of the mixture used being 100 parts by weight, the amount of the solvent used in the polymerization reaction ranges from 200 parts by weight to 2,000 parts by weight; more preferably, from 300 parts by weight to 1,800 parts by weight.

[0085] In particular, in the above-mentioned polymerization reaction, a proper amount of poor solvent can be used as a solvent, as long as the polyamic acid is not precipitated. The poor solvent can be used alone or in combination, and the poor solvent includes but is not limited to (1) alcohols: methanol, ethanol, isopropanol, cyclohexanol, ethylene glycol, propylene glycol, 1,4-butanediol or triethylene glycol, etc.; (2) ketones: acetone, methyl ethyl ketone, methyl isobutyl ketone or cyclohexanone, etc.; (3) esters: methyl acetate, ethyl acetate, butyl acetate, diethyl oxalate, diethyl malonate or ethylene glycol ethyl ether acetate, etc.; (4) ethers: diethyl ether, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol n-propyl ether, ethylene glycol isopropyl ether, ethylene glycol n-butyl ether, ethylene glycol dimethyl ether or diethylene glycol dimethyl ether, etc.; (5) halogenated hydrocarbons: dichloromethane, 1,2-dichloroethane, 1,4-dichlorobutane, trichloroethane, chlorobenzene or o-dichlorobenzene, etc.; (6) hydrocarbons: tetrahydrofuran, hexane, heptane, octane, benzene, toluene or xylene, etc.; or (7) any combination of the above. Preferably, based on the total amount of the diamine component used being 100 parts by weight, the amount of the lean solvent used is in the range of 0 to 60 parts by weight; more preferably, the amount of the lean solvent used is in the range of 0 to 50 parts by weight.

[0086] [Method for producing polyimide]

[0087] The preparation method of polyimide comprises the following steps: dissolving a mixture in a solvent, wherein the mixture includes a tetracarboxylic dianhydride component (b1) and a diamine component (b2), performing a polymerization reaction to form polyamic acid, and further heating and performing a dehydration closed cycle reaction in the presence of a dehydrating agent and a catalyst, so that the amic acid functional group generated during the polymerization reaction is converted into an imide functional group (i.e., imidization).

[0088] The polymerization reaction and the dehydration dead cycle reaction can adopt the reaction temperature and reaction time of the previous operation in the relevant field. Preferably, the operating temperature range of the polymerization reaction is 0°C to 100°C. Preferably, the operating time range of the polymerization reaction is 1 hour to 24 hours. Preferably, the operating temperature range of the dehydration dead cycle reaction is 30°C to 200°C, and the operating time range of the dehydration dead cycle reaction is 0.5 hour to 50 hours.

[0089] Specific examples of the solvent used in the dehydration dead cycle reaction include, but are not limited to, N-methyl-2-pyrrolidone, γ-butyrolactone, γ-butyrolactam, 4-hydroxy-4-methyl-2-pentanone, ethylene glycol monomethyl ether, butyl lactate, butyl acetate, methyl methoxypropionate, ethyl ethoxypropionate, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol n-propyl ether, ethylene glycol isopropyl ether, ethylene glycol n-butyl ether, ethylene glycol dimethyl ether, ethylene glycol ethyl ether acetate, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, or N,N-dimethylformamide or N,N-dimethylacetamide (NN-dimethyl acetamide), etc. Preferably, based on 100 parts by weight of polyamic acid, the amount of the solvent used in the dehydration dead cycle reaction ranges from 200 parts by weight to 2,000 parts by weight. More preferably, the amount of the solvent used in the dehydration dead cycle reaction ranges from 300 parts by weight to 1,800 parts by weight.

[0090] The dehydrating agent used in the dehydration dead cycle reaction is selected from anhydride compounds: acetic anhydride, propionic anhydride or trifluoroacetic anhydride, etc. Based on 1 mol of polyamic acid resin, the amount of the dehydrating agent used ranges from 0.01 mol to 20 mol. The catalyst used in the dehydration dead cycle reaction is selected from (1) pyridine compounds: pyridine, trimethylpyridine or dimethylpyridine, etc.; (2) tertiary amine compounds: triethylamine, etc. Based on 1 mol of the dehydrating agent, the amount of the catalyst used ranges from 0.5 mol to 10 mol.

[0091] The polymer (B) of the present invention has a weight average molecular weight of 10,000 to 90,000, preferably 12,000 to 75,000, and more preferably 15,000 to 60,000, as measured by gel permeation chromatography (GPC) and calculated based on polystyrene.

[0092] [Insoluble liquid crystal polyester (C)]

[0093] The polymer film of the present invention further comprises an insoluble liquid crystal polyester (C). If the insoluble liquid crystal polyester (C) is not used, the polymer film cannot achieve low moisture permeability. In some embodiments, the insoluble liquid crystal polyester (C) comprises at least one of the structural unit represented by the following formula (c1), the structural unit represented by the following formula (c2), and the structural unit represented by the following formula (c3).

[0094] -O-Ar 4 -CO-(c1)

[0095] -CO-Ar 5 -CO-(c2)

[0096] -O-Ar 6 -O-(c3)

[0097] In formula (c1), Ar 4 represents 2,6-naphthalenediyl, 1,4-phenylene or 4,4'-biphenylene;

[0098] In formula (c2) and formula (c3), Ar 5 and Ar 6 are independently 2,6-naphthalenediyl, 1,4-phenylene, 1,3-phenylene or 4,4'-biphenylene, wherein Ar 4 ,Ar 5 or Ar 6 The hydrogen atoms in the aforementioned groups shown in the figure may be substituted by halogen atoms, alkyl groups having 1 to 10 carbon atoms or aromatic groups having 6 to 20 carbon atoms, and the aforementioned halogen atoms may be fluorine atoms, chlorine atoms, bromine atoms or iodine atoms. In addition, the aforementioned alkyl groups may be linear, branched or cyclic, and may be methyl, ethyl, propyl, butyl, hexyl, octyl or decyl. In addition, the aforementioned aromatic groups may be phenyl or naphthyl.

[0099] In some embodiments, the flow starting temperature of the insoluble liquid crystal polyester (C) is preferably 260°C to 380°C, more preferably 280°C to 380°C, even more preferably 290°C to 380°C, and particularly preferably 295°C to 350°C. In other embodiments, the flow starting temperature of the insoluble liquid crystal polyester (C) may be 260°C to 280°C, or 260°C to 275°C. If the flow starting temperature of the insoluble liquid crystal polyester (C) is within the above range, the heat resistance of the liquid composition of the polymer film can be improved, and the molding temperature will not become too high, and it is not easy to be thermally degraded.

[0100] It should be noted that the flow starting temperature is the temperature at which the melt viscosity shows 4800 Pa.s when the liquid crystal polyester is extruded from a nozzle at a heating rate of 4°C / min under a load of 9.8 MPa using a capillary rheometer equipped with a die having an inner diameter of 1 mm and a length of 10 mm (for example, refer to Naoyuki Koide's "Liquid Crystal Polymers - Synthesis, Molding, and Applications", pages 95 to 105, CMC, published on June 5, 1987).

[0101] In the insoluble liquid crystal polyester (C), the structural unit represented by the formula (c1) is a structural unit derived from a specific aromatic hydroxycarboxylic acid.

[0102] Relative to the total content of all structural units constituting the insoluble liquid crystal polyester (C), the content of the structural unit represented by formula (c1) is preferably 30 mol % to 80 mol %, more preferably 40 mol % to 70 mol %, and even more preferably 45 mol % to 65 mol %.

[0103] In the insoluble liquid crystal polyester (C), the structural unit represented by the formula (c2) is a structural unit derived from a specific aromatic dicarboxylic acid.

[0104] Relative to the total content of all structural units constituting the insoluble liquid crystal polyester (C), the content of the structural unit represented by formula (c2) is preferably 10 mol % to 35 mol %, more preferably 15 mol % to 30 mol %, and even more preferably 17.5 mol % to 27.5 mol %.

[0105] In the insoluble liquid crystal polyester (C), the structural unit represented by the formula (c3) is a structural unit derived from a specific aromatic diol.

[0106] Relative to the total content of all structural units constituting the insoluble liquid crystal polyester (C), the content of the structural unit represented by formula (c3) is preferably 10 mol% to 35 mol%, more preferably 15 mol% to 30 mol%, and more preferably 17.5 mol% to 27.5 mol%. Among them, the content of the structural unit represented by formula (c2) is preferably substantially equal to the content of the structural unit represented by formula (c3). The total content of the structural unit represented by formula (c1), the structural unit represented by formula (c2), and the structural unit represented by formula (c3) does not exceed 100 mol%.

[0107] In order to rapidly carry out melt polycondensation of the monomers, it is preferred to use ester-forming derivatives of the above-mentioned monomers.

[0108] Here, specific examples of the ester-forming derivatives include compounds having a carboxyl group such as aromatic hydroxycarboxylic acid or aromatic dicarboxylic acid, and compounds in which the carboxyl group can be converted into a haloformyl group, an acyloxycarbonyl group, an alkoxycarbonyl group or an aryloxycarbonyl group.

[0109] Furthermore, as long as it is a compound having a hydroxyl group such as an aromatic hydroxycarboxylic acid or an aromatic diol, for example, a compound having a hydroxyl group may be converted into an acyloxy group. Among them, a compound having a hydroxyl group converted into an acyloxy group is preferably used. That is, the ester-forming derivative of an aromatic hydroxycarboxylic acid is preferably an aromatic acyloxycarboxylic acid in which the hydroxyl group is acylated. Furthermore, the ester-forming derivative of an aromatic diol is preferably an aromatic diacyloxy compound in which the hydroxyl group is acylated. Acylation is preferably acetylated with acetic anhydride, and the ester-forming derivative formed by acetylation may be subjected to deacetylating polycondensation.

[0110] [Polymer film and method for producing the same]

[0111] The polymer film of the present invention comprises a soluble liquid crystal polyester (A), a polymer (B) and an insoluble liquid crystal polyester (C), and the insoluble liquid crystal polyester (C) is dispersed in the liquid crystal polyester liquid composition.

[0112] Based on the polymer film being 100wt%, the content of the soluble liquid crystal polyester (A) is 20wt% to 90wt%, preferably 25wt% to 85wt%, more preferably 30wt% to 80wt%; the content of the polymer (B) is not less than 3wt%, preferably not less than 4wt%, more preferably not less than 5wt%; the content of the insoluble liquid crystal polyester (C) is 5wt% to 70wt%, preferably 7wt% to 65wt%, 10wt% to 60wt%.

[0113] In addition, the term "dispersed" means a state in which particles are distributed in the film without agglomeration. The polymer film can be produced by the following method.

[0114] The polymer film is manufactured by a manufacturing method comprising the following steps, namely:

[0115] The aforementioned liquid crystal polyester liquid composition of the present invention is cast on a supporting substrate (e.g., metal foil); the solvent is removed from the aforementioned liquid crystal polyester liquid composition, thereby obtaining a laminate having the aforementioned supporting substrate (e.g., metal foil) and a polymer film precursor; the aforementioned laminate obtained by removing the aforementioned solvent is heat-treated, thereby obtaining a laminate having the aforementioned supporting substrate (e.g., metal foil) and a polymer film.

[0116] The method of film casting the aforementioned liquid crystal polyester liquid composition can be, for example, a method of casting on a supporting substrate by various means such as cast coating, roll coating, dip coating, spray coating, spin coating, curtain coating, slot coating, screen printing, etc.

[0117] In some embodiments, the support substrate is preferably a metal foil, such as a copper foil. In some embodiments, the thickness of the support substrate is preferably 7 to 35 μm.

[0118] The method for removing the solvent is not particularly limited, but it is preferably carried out by evaporating the solvent. The method for evaporating the solvent can include heating, decompression, ventilation and the like. From the perspective of improving production efficiency and easy handling, heating evaporation is preferred, and ventilation and heating evaporation are more preferred. At this time (when removing the solvent), the heating conditions preferably include preliminary drying at 60°C to 200°C for 10 minutes to 2 hours, and heat treatment at 200°C to 400°C for 30 minutes to 5 hours.

[0119] The heat treatment performed to obtain a laminate having a supporting substrate (metal foil) and a polymer film is preferably performed at 250° C. to 340° C. for 1 to 12 hours.

[0120] [Example]

[0121] 1. Synthesis Example of Soluble Liquid Crystal Polyester (A)

[0122] Synthesis Example A-1

[0123] Nitrogen was introduced into a reaction vessel equipped with a nitrogen inlet, a stirrer, a heater, a condenser and a thermometer, and then 5.0 mol of 6-hydroxy-2-naphthoic acid (a1-1), 2.5 mol of terephthalic acid (a2-1), 1.5 mol of 3-hydroxyacetanilide (a3-1), 1.0 mol of 4,4'-biphenol (a4-1) and 11.0 mol of acetic anhydride were added.

[0124] Next, the above components are slowly stirred under a nitrogen stream to raise the temperature of the solution to 140°C, and react at this temperature for 3 hours. Then, the by-product acetic acid and unreacted acetic anhydride are distilled off from the reaction system, and the solution is heated to 300°C at a heating rate of 1.0°C / min, and then decompressed at 300°C. After reacting at 300°C for 1 hour, the product is taken out of the reaction vessel and cooled to room temperature. The cooled product is crushed with a pulverizer to obtain a powdered soluble liquid crystal polyester (A-1).

[0125] 10 g of the powdery soluble liquid crystal polyester (A-1) was added to 90 g of N-methyl-2-pyrrolidone and heated to 160° C. to completely dissolve it, thereby obtaining a brown transparent solution.

[0126] Synthesis Examples A-2 to A-5 and Comparative Synthesis Examples A'-1 and A'-2

[0127] Synthesis Examples A-2 to A-5 and Comparative Synthesis Examples A'-1 and A'-2 use the same preparation method as the preparation method of the liquid crystal polyester (A-1) of Synthesis Example A-1, except that Synthesis Examples A-2 to A-5 and Comparative Synthesis Examples A'-1 and A'-2 change the type and amount of the first mixture, and Comparative Synthesis Example A'-1 does not use aromatic diol (a4), and Comparative Synthesis Example A'-2 does not use aromatic amine (a3) ​​having phenolic hydroxyl groups. The formulas are shown in Table 1, which are not described here.

[0128] 2. Synthesis Example of Polymer (B)

[0129] Synthesis Example B-1

[0130] A nitrogen inlet, a stirrer, a condenser and a thermometer are set on a four-necked conical flask with a volume of 500 ml, and nitrogen is introduced. Then, 0.025 mol of p-aminophenyl benzoate (abbreviated as b2-1-1) and 70 grams of N-methyl-2-pyrrolidone (abbreviated as NMP) are added, and stirred at room temperature until dissolved. Next, 0.024 mol of p-phenylene-diphenyltrimethylolpropane tetracarboxylic dianhydride (abbreviated as b1-1-1) and 30 grams of NMP are added, and the reaction is carried out at room temperature for 2 hours. After the reaction is completed, the reaction solution is poured into 1500 ml of water to precipitate the polymer, the obtained polymer is filtered, and the steps of washing and filtering are repeated three times with methanol. After that, the product is placed in a vacuum oven and dried at a temperature of 60°C to obtain polymer (B-1).

[0131] Synthesis Examples B-2 to B-5 and Comparative Synthesis Example B'-1

[0132] Synthesis Examples B-2 to B-5 and Comparative Synthesis Example B'-1 use the same preparation method as the preparation method of the polymer (B-1) of Synthesis Example B-1, except that the type and amount of the second mixture are changed in Synthesis Examples B-2 to B-5 and Comparative Synthesis Example B'-1, and Comparative Synthesis Example B'-1 uses other tetracarboxylic dianhydride compounds (b1-2) without ester groups and other diamine compounds (b2-2) without ester groups. The formulas are shown in Table 2, which are not described in detail here.

[0133] 3. Synthesis Example of Insoluble Liquid Crystal Polyester (C)

[0134] In a reactor equipped with a stirring device, a torque meter, a nitrogen inlet pipe, a thermometer and a reflux cooler, 5.4 mol of 6-hydroxy-2-naphthoic acid (abbreviated as C1-1), 1.7 mol of 2,6-naphthalenedicarboxylic acid (abbreviated as C2-2), 0.5 mol of terephthalic acid (abbreviated as C2-1), 2.4 mol of hydroquinone (abbreviated as C3-2), 12 mol of acetic anhydride and 0.17 g of 1-methylimidazole as a catalyst were added. After replacing the gas in the reactor with nitrogen, the temperature was raised from room temperature to 145° C. over 15 minutes while stirring under a nitrogen flow, and refluxed at 145° C. for 1 hour.

[0135] Then, while distilling off the by-product acetic acid and unreacted acetic anhydride, the temperature was raised from 145°C to 310°C over 3 hours and 30 minutes. After being kept at 310°C for 3 hours, the solid insoluble liquid crystal polyester (C-1) was taken out and the insoluble liquid crystal polyester (C-1) was cooled to room temperature (23°C). The flow starting temperature of the insoluble liquid crystal polyester (C-1) was 265°C.

[0136] Synthesis Example C-2 and Synthesis Example C-3

[0137] Synthesis Example C-2 and Synthesis Example C-3 are prepared by the same method as the preparation method of the insoluble liquid crystal polyester (C-1) of Synthesis Example C-1, except that the types and amounts of reactants are changed in Synthesis Example C-2 and Synthesis Example C-3. The formulas are shown in Table 3, which are not described in detail here.

[0138] Examples of liquid compositions

[0139] Example 1

[0140] Weigh 45 grams of a 10 wt% solution of a soluble liquid crystal polyester (A-1), add 1.9 grams of a polymer (B-1), stir evenly, add 2.7 grams of an insoluble liquid crystal polyester (C-1) and an appropriate amount of NMP, and adjust the solid content (TS) to 13 wt%. After stirring and degassing, a liquid composition can be obtained.

[0141] Examples 2 to 6 and Comparative Examples 1 to 5

[0142] Examples 2 to 6 and Comparative Examples 1 to 5 are prepared using the same method as Example 1. The difference lies in the types and amounts of the soluble liquid crystal polyester (A), polymer (B) and insoluble liquid crystal polyester (C) used in Examples 2 to 6 and Comparative Examples 1 to 5. The formulations and evaluation results are shown in Table 4, which are not described in detail here.

[0143] [Evaluation method]

[0144] Flexibility

[0145] The liquid composition is cast on the electrolytic copper foil using a coating device, and then heated at 120°C for 30 minutes using a high-temperature hot air dryer to remove the solvent. The copper foil substrate with a polymer film is then obtained after heat treatment at 330°C for 1 hour.

[0146] The test was conducted using a Toyo Seiki Seisaku-sho MIT bending tester (in accordance with JIS-P8815 rules) at a bending angle of 135° (R=0.38) to measure the number of bends until the film broke.

[0147] ◎: Bending times ≥ 30,000 times

[0148] ○: 20,000 times ≤ bending times < 30,000 times

[0149] Δ: 10,000 times ≤ bending times < 20,000 times

[0150] ×: Bending times < 10,000 times

[0151] Coating properties

[0152] The above-mentioned liquid composition was cast on a glass substrate using an applicator, and the surface of the coating film was observed. The evaluation criteria were as follows.

[0153] ◎: After coating, the surface is flat and no irregular lines appear

[0154] ○: The surface is flat after coating, with only a few irregular lines.

[0155] Δ: The surface is flat after coating, but there are serious irregular lines.

[0156] ×: The surface is uneven after coating, and there are serious irregular lines and particles.

[0157] Moisture Permeability

[0158] The liquid composition is cast on an electrolytic copper foil using an applicator, and then heated at 120°C for 30 minutes using a high-temperature hot air dryer to remove the solvent. The copper foil substrate with a thin film is then obtained after heat treatment at 330°C for 1 hour.

[0159] Next, after removing the copper foil, a 50 mm × 50 mm sample was cut out from the film and measured according to JIS K7126A method (differential pressure method) using an air permeability / moisture permeability measuring device (GTR-10X, manufactured by GTR Tech Co.) at a temperature of 40°C and a relative humidity of 90%. The moisture permeability (unit: g / m 2 ·24hr) The evaluation criteria are as follows.

[0160] ◎: Moisture permeability ≤ 0.1

[0161] ○: 0.1<Moisture permeability≤0.15

[0162] Δ: 0.15<Moisture permeability≤0.2

[0163] ×: Moisture permeability>0.2

[0164] Table 1

[0165]

[0166] a1-16-Hydroxy-2-naphthoic acid

[0167] a1-2-parahydroxybenzoic acid

[0168] a1-3-hydroxybenzoic acid

[0169] a2-1 Terephthalic acid

[0170] a2-2 Isophthalic acid

[0171] a2-3,2,6-Naphthalenedicarboxylic acid

[0172] a3-13-Hydroxyacetaniline

[0173] a3-24-Hydroxyacetaniline

[0174] a3-33-aminophenol

[0175] a3-44-aminophenol

[0176] a3-54-amino-4′-hydroxybiphenyl

[0177] a4-14,4'-Biphenylene glycol

[0178] a4-24,4′-dihydroxydiphenyl ether

[0179] a4-34,4'-dihydroxydiphenylmethane

[0180] a4-4 Hydroquinone

[0181] Table 2

[0182]

[0183] b1-1-1-p-phenylene-bis(triphenylene) ester tetracarboxylic dianhydride

[0184] b1-1-2 Ethylene-bis(triphenylene) ester tetracarboxylic dianhydride

[0185] b1-1-3 (4-phthalic anhydride) methyloxy-4-phthalic acid ester

[0186] b1-2-1 Pyromellitic dianhydride

[0187] b2-1-1 p-aminobenzoic acid p-aminophenyl ester

[0188] b2-1-2 Bis(p-aminophenyl) terephthalate

[0189] b2-1-3[4-(4-aminobenzyl)oxyphenyl]4-aminobenzoate

[0190] b2-2-2 p-phenylenediamine

[0191] Table 3

[0192]

[0193] a1-16-Hydroxy-2-naphthoic acid

[0194] a1-2-parahydroxybenzoic acid

[0195] a2-1 Terephthalic acid

[0196] a2-3,2,6-Naphthalenedicarboxylic acid

[0197] a4-14,4′-biphenylene glycol

[0198] a4-3 Hydroquinone

[0199] Table 4

[0200]

[0201] It can be seen from the above results that if the aromatic diol (a4) is not added during the synthesis of the soluble liquid crystal polyester (A), the obtained liquid composition will have poor flexibility and coating properties when used in a polymer film.

[0202] In the synthesis of the soluble liquid crystal polyester (A), if the aromatic amine (a3) ​​having a phenolic hydroxyl group is not added, the coating properties of the obtained liquid composition when used for a polymer film are poor.

[0203] Furthermore, the liquid composition formed without using the polymer (B) has poor flexibility after being coated on a polymer film.

[0204] If the ester-containing tetracarboxylic dianhydride (b1-1) or the ester-containing diamine (b2-1) is not used in the synthesis of the polymer (B), the compatibility between the soluble liquid crystal polyester (A) and the polymer (B) is poor, resulting in poor coating properties of the liquid composition.

[0205] Secondly, if the liquid composition formed by the soluble liquid crystal polyester (A) prepared by using the aromatic diol (a4) with a specific structure is used, the flexibility of the polymer film formed by it is better.

[0206] If a liquid composition formed by using a polymer (B) prepared from an ester-containing tetracarboxylic dianhydride (b1-1) and an ester-containing diamine (b2-1) and a liquid crystal polyester (A) is used, its coating properties on a polymer film are better.

[0207] If the insoluble liquid crystal polyester (C) is not used, the moisture permeability of the polymer film formed from the liquid composition is too high.

[0208] Although the present invention uses specific compounds, compositions, reaction conditions, processes, analysis methods or specific instruments as examples to explain the insulated wire and its manufacturing method, coil and electronic device of the present invention, anyone with ordinary knowledge in the technical field to which the present invention belongs will understand that the present invention is not limited to these. Without departing from the spirit and scope of the present invention, the insulated wire and its manufacturing method, coil and electronic device of the present invention may also be carried out using other compounds, compositions, reaction conditions, processes, analysis methods or instruments.

[0209] Although the present invention has been disclosed as above with several embodiments, they are not intended to limit the present invention. Anyone with ordinary knowledge in the technical field to which the present invention belongs can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the scope of the attached patent application.

Claims

1. A polymer film, characterized in that: Include: A soluble liquid crystal polyester (A), wherein the soluble liquid crystal polyester (A) is obtained by reacting a first mixture, wherein the first mixture comprises an aromatic hydroxycarboxylic acid (a1), an aromatic dicarboxylic acid (a2), an aromatic amine having a phenolic hydroxyl group (a3) ​​and an aromatic diol (a4); A polymer (B), wherein the polymer (B) is at least one selected from the group consisting of a polyimide precursor and an imidized polymer of the polyimide precursor, and the polymer (B) is obtained by reacting a second mixture, and the second mixture comprises a tetracarboxylic dianhydride component (b1) and a diamine component (b2); and Insoluble liquid crystal polyester (C).

2. The polymer film according to claim 1, characterized in that: The soluble liquid crystal polyester (A) comprises at least one of the structural units of the following formula (a1'), formula (a2'), formula (a3') and formula (a4'), -O-Ar 1 -CO- (a1') -CO-Ar 2 -CO- (a2') <h2 style=";text-align:left;direction:ltr">-NH-Ar<h2 style=";text-align:left;direction:ltr"> 3 <h2 style=";text-align:left;direction:ltr"> -O- (a3') -O-Ar 3 -O- (a4') In formula (a1'), Ar 1 represents a phenylene group, a naphthylene group or a biphenylene group; In formula (a2'), Ar 2 represents a phenylene group, a naphthylene group, a biphenylene group, or a group formed by condensation of a plurality of aromatic groups; and In formula (a3') and formula (a4'), Ar 3 It represents a phenylene group or a group formed by condensation of a plurality of aromatic groups.

3. The polymer film according to claim 1, characterized in that: The aromatic amine (a3) ​​having a phenolic hydroxyl group includes an aromatic hydroxyamide.

4. The polymer film according to claim 1, characterized in that: The polymer (B) includes an ester structure.

5. The polymer film according to claim 1, characterized in that: The tetracarboxylic dianhydride component (b1) includes a tetracarboxylic dianhydride compound (b1-1) containing an ester group.

6. The polymer film according to claim 1, characterized in that: The diamine component (b2) includes an ester group-containing diamine compound (b2-1).

7. The polymer film according to claim 1, characterized in that: Based on 100 wt % of the polymer film, the content of the soluble liquid crystal polyester (A) is 20 wt % to 90 wt %.

8. The polymer film according to claim 1, characterized in that: Based on 100 wt % of the polymer film, the content of the polymer (B) is not less than 3 wt %.

9. The polymer film according to claim 1, characterized in that: Based on 100 wt % of the polymer film, the content of the insoluble liquid crystal polyester (C) is 5 wt % to 70 wt %.

10. The polymer film according to claim 1, characterized in that: The aromatic diol (a4) is at least one compound selected from the group consisting of compounds including the following structural units.

11. A method for producing a polymer film, characterized in that: To obtain the polymer film as claimed in any one of claims 1 to 10, wherein the method for manufacturing the polymer film comprises: A coating step for coating a liquid composition on a substrate, wherein the liquid composition comprises the soluble liquid crystal polyester (A), the polymer (B), the insoluble liquid crystal polyester (C) and a solvent; as well as A heating step is performed to heat the substrate coated with the liquid composition, wherein the heating temperature of the heating step is greater than 300°C.

Citation Information

Cited By

  • Production method of polyester-polyimide / polyamic acid copolymer, and polyester-polyimide / polyamic acid copolymer

    JP2023183864A